Classification of lesion area in stroke patients during the subacute phase: A multiparametric MRI study. Issue 5 (14th November 2013) - Artzi, Moran; Aizenstein, Orna; Jonas‐Kimchi, Tali; Bornstein, Natan; Shopin, Ludmila; Hallevi, Hen; Ben Bashat, Dafna; on behalf of the STIR; VISTA Imaging collaborators
<x xml:space="preserve">Abstract</x> Purpose Stroke imaging studies during the acute phase are likely to precede several vascular brain mechanisms, which have an important role in patient outcome. The aim of this study was to identify within the lesion area during the subacute phase (≥1 day) reactive tissue, which may have the potential for recovery. Methods Twenty seven stroke patients from two cohorts were included. MRI performed during the subacute phase included conventional, perfusion and diffusion imaging. In cohort I, unsupervised multiparametric classification of the lesion area was performed. In cohort II threshold based classification was performed during the subacute phase, and radiological outcome was assessed at follow‐up scan. Results Three tissue classes were identified in cohort I, referred to as irreversibly damaged, intermediary, and reactive tissue. Based on threshold values defined in cohort I, the reactive tissue was identified in 11/13 patients in cohort II, and showed tissue preservation/partial recovery in 9/11 patients at follow‐up scan. The irreversibly damaged tissue was identified in 7/13 patients in cohort II, and predicted tissue necrosis in all cases. Conclusion Identification of reactive tissue following stroke during the subacute phase can improve radiological assessment, contribute to the understanding of brain recovery processes and has implications for new therapeutic approaches. Magn Reson Med 72:1381–1388, 2014. © 2013 Wiley Periodicals, Inc.